Faktor-faktor yang Mempengaruhi Kepuasan Konsumen Kopi Bubuk Wamor Khas Labuan Bajo Manggarai Barat - Jandu, Inosensius Harmin; Hudin, Robertus; Budiman, Nikolaus Dionesius (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The need for coffee is almost the same as the need for other important agricultural commodities. Indonesia is one of the countries with the highest coffee consumption, so coffee has become an inseparable part of people's lives. Therefore, its existence is very important. Of course, good coffee is coffee that always maintains its quality and is delicious to consume. Wamor ground coffee is an MSME that operates in the field of processing coffee into ground coffee. This research aims to find out what factors influence consumer satisfaction with Wamor coffee. The research method uses qualitative and quantitative approaches. Data collection techniques use survey methods and questionnaire instruments. The number of samples used was 50 people. The research results of the six variables used to measure consumer satisfaction with wamor powdered coffee, namely taste, ease of product access, emotional relationships, have a significant positive influence, while product continuity, service, and affordable prices have a positive but not significant influence on consumer satisfaction with wamor powdered coffee. Thus, this research provides valuable insight for Wamor Coffee UMKM in understanding their consumers' preferences and needs, which can be used as a basis for improving their products and services to better meet consumer expectations.